Hubungan Kekerabatan Fenetik Jamur Shiitake (Lentinula edodes (Berk.) Pegler) berdasarkan Karakter Morfologi - Nuraeni Ekowati; Rina Sri Kasiamdari; Nursamsi Pusposendjojo; C. J. Soegihardjo (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2011)
Phenetic relationship of shiitake mushroom (Lentinula edodes (Berk.) Pegler) cultivated in Indonesia especially in Java is still undisclosed. In order to increase adaptability and high production most of cultivators in Indonesia make inter-isolates breeding. Consequently  L. edodes isolates grown in Indonesia may have morphological and genetic diversity. Diversity among the isolates of L.edodes can be determined by morphological and molecular assessments. Isolates originating from different locations can show specific morphological characters, and requires more in-depth assessment of the macroscopic and microscopic morphological characters. Four  L.edodes isolates from Malang, Cianjur, Lembang and Yogyakarta were understudy to determine their morphological characters and phenetic relationship. Degree of similarity between the isolates was carried out through numerical taxonomy approach and the data obtained were analyzed using the Numerical taxonomy program and multivariate analysis system, version 2.1. The results showed that there was diversity of morphology of the four isolates and based on the results of data analysis obtained, the degree of similarity between the isolates ranged between 83-95%. Isolates of L. edodes from Malang to Cianjur showed the closest phenetic relationship (95%) and isolates from Malang to Yogyakarta showed the most distant phenetic relationship (83%). Based on the morphological characters obtained from this research revealed the diversity and phenetic relationship among the four isolates of L. edodes.